2010
DOI: 10.1371/journal.pone.0010738
|View full text |Cite
|
Sign up to set email alerts
|

Large-Range Movements of Neotropical Orchid Bees Observed via Radio Telemetry

Abstract: Neotropical orchid bees (Euglossini) are often cited as classic examples of trapline-foragers with potentially extensive foraging ranges. If long-distance movements are habitual, rare plants in widely scattered locations may benefit from euglossine pollination services. Here we report the first successful use of micro radio telemetry to track the movement of an insect pollinator in a complex and forested environment. Our results indicate that individual male orchid bees (Exaerete frontalis) habitually use larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(136 citation statements)
references
References 39 publications
5
118
0
8
Order By: Relevance
“…It is possible, then, that orchid bees vague through both environments, exploiting whatever resources they can find in each of them. For example, riparian forests would be important for orchid bees, offering them nesting sites, food resources and protection against intense solar radiation and winds (Neves & Viana 1999, Wikelski et al, 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible, then, that orchid bees vague through both environments, exploiting whatever resources they can find in each of them. For example, riparian forests would be important for orchid bees, offering them nesting sites, food resources and protection against intense solar radiation and winds (Neves & Viana 1999, Wikelski et al, 2010.…”
Section: Discussionmentioning
confidence: 99%
“…First, relatively small forest patches, even in urban areas, can sustain viable populations of at least some species of these insects (Bezerra & Martins, 2001;Storti et al, 2013). Second, as vagile, long-flighted organisms (Wikelski et al, 2010), orchid bees are able to fly many kilometers daily in search for food and other resources (Wikelski et al, 2010), what theoretically presumes a relatively high ability to colonize different kinds of environments and finally, their males are easily attracted to synthetic compounds that mimic floral fragrances, making field studies easy to conduct.…”
Section: Introductionmentioning
confidence: 99%
“…Plebeia and Tetragonisca) often fly distances of up to 1 km while flight distances for larger Melipona species can be > 2 km (Araújo et al, 2004). The largest orchid bees (Eulaema; 18-31 mm) can fly up to 23 km, including the crossing of unsuitable matrix habitat such as open waters for several kilometres (Janzen, 1971;Wikelski et al, 2010). In this bee group, patrolling flights of males can reach long distances and thus disperse pollen among fragmented plant populations.…”
Section: Box 4 Bees As Network Nodesmentioning
confidence: 99%
“…The survey of euglossine bees (Darrault et al, 2006) and other organisms (Pôrto et al, 2005) at 12 fragments in the CEP showed that the fauna of the largest forest remnant was not significantly richer or more diverse than the smaller ones within a local complex of forest fragments separated often less than 100 m by areas of varying soil use and conservation degree, which provide a permeable matrix for these long-distance pollinators. Males of Exaerete frontalis can forage on 42-115 ha of rainforest and fly up to 5 km away from their core areas (Wikelski et al, 2010). Males of common species (Eg.…”
Section: Conservationmentioning
confidence: 99%